High-order coupled cluster method calculations of spontaneous symmetry breaking in the spin-half one-dimensional J₁-J₂ model - Farnell, D.J.J. (Condensed Matter Physics, 2009)
In this article we present new formalism for high-order coupled cluster method (CCM) calculations for generalized
ground-state expectation values and the excited states of quantum magnetic systems with spin
quantum number s ≥ 1/2 . We use high-order CCM to demonstrate spontaneous symmetry breaking in the
spin-half J₁ J₂ model for the linear chain using the coupled cluster method (CCM). We show that we are able
to reproduce exactly the dimerized ground (ket) state at the Majumdar-Ghosh point (J₂/J₁ = 1/2 ) using a N´eel
model state. We show that the onset of dimerized phase is indicated by a bifurcation of the nearest-neighbour
ket- and bra-state correlation coefficients for the nearest-neighbour N´eel model state. We show that groundstate
energies are in good agreement with the results of exact diagonalizations of nite-length chains across
this entire regime (i. e., J₁ > 0 and J₂ ≤ 1/2 ). The effects of the bifurcation point are also observed for the sublattice
magnetization for the nearest-neighbour model state. Finally, we use the new formalism for the excited
state in order to obtain the excitation energy as a function of J₂/J₁ for the nearest-neighbour model state by
solving up to the LSUB14 level of approximation. We obtain an extrapolated value for the excited-state energy
gap of -0:0036 at J₂/J₁ = 0:0 and of 0:2310 at J₂/J₁ = 0:5. We show that an excitation energy gap opens
up at J₂/J₁ ≈ 0:24, although the gap only becomes large at J₂/J₁ ≈ 0:4. У цiй статтi ми представляємо новий формалiзм розрахункiв методом взаємодiючих кластерiв (МВК) у вищих порядках для “узагальнених” середнiх значень в основному станi i збуджених станiв квантових магнiтних систем зi спiновим квантовим числом s ≥ 1/2. Ми використовуємо МВК у вищих наближеннях, щоб продемонструвати спонтанне порушення симетрiї у спiн-половина J₁-J₂ моделi на лiнiйному ланцюжку. Ми показуємо, що можна вiдтворити точно димеризований основний (кет) стан у точцi Маджумдара-Гоша (J₂/J₁ = 1/2), використовуючи як модельний стан стан Нiеля. Ми показуємо, що на встановлення димеризованої фази вказує бiфуркацiя кореляцiйних коефiцiєнтiв для кет- i бра-станiв для модельного стану Нiеля. Ми показуємо, що енергiя основного стану добре узгоджується iз результатами точної дiагоналiзацiї ланцюжкiв скiнченої довжини у цьому всьому режимi (тобто J₁ > 0 і J₂ ≤ 1/2). Ефекти точки бiфуркацiї також спостерiгаються у намагнiченостi пiдгратки для модельного стану Нiеля. Нарештi ми використовуємо новий формалiзм для збуджених станiв, щоб отримати енергiю збудження як функцiю J₂/J₁ для модельного стану Нiеля, шукаючи розв’язок аж до наближнення рiвня LSUB14. Ми отримуємо екстрапольоване значення для щiлини для енергiї збудження -0:0036 при J₂/J₁ = 0:0 i 0:2310 при J₂/J₁ = 0:5. Ми показуємо, що енергетична щiлина для збудження вiдкривається при J₂/J₁ ≈ 0:24, хоча щiлина стає великою лише при J₂/J₁ ≈ 0:4..